SISTEM INFORMASI GEOGRAFIS YAYASAN KRISTEN DAN PENDIDIKAN KRISTEN - Ricky Ricky (Jurnal Ilmu Komputer dan Sistem Informasi, 2013)
Geographic Information System technology is a technology that is growing on the geographical today. Current information about the means of an institution in a region that is much sought after by the public, such as location information, status, and facilities of the institution. One of the facilities are pretty effective dissemination of information that is the internet media. To assist in accelerating the process of presenting the information then made a web-based Geographic Information System.Objective of this application is to map and display the locations of an existing institution in Indonesia, allow a user to find the location of an institution quickly and accurately, and displays the data from the location of the institution in full. In making this Geographic Information Systems discussed the creation of Geographic Information Systems and the Christian Foundation for Christian Education by using ArcView GIS 3.3 applications. The methodology used in this application is a program making Prototyping Methodology. Modeling Spatial Data used was Vector Data Model. Key wordsMap, ArcView, Prototyping, dan Vector Data Model.